1981
DOI: 10.1021/ja00401a018
|View full text |Cite
|
Sign up to set email alerts
|

Structures, spectroscopy, and a mechanism of formation of linked-norbornadiene complexes of ruthenium(II). Interaction of ruthenium(II) with alicyclic hydrogen atoms

Abstract: The electronic structure of M O (~-B U S )~, as studied by a UV photoelectron spectroscopy and X,-SW MO calculations, will be a subject of a separate paper. ~~Since the molecular structure of tetrakis(alcoho1ato)molybdenum( IV) compound has not been studied by X-ray diffraction, of the rather rare class of mononuclear tetracoordinate d2 species. Acknowledgment. We thank Japan Synthetic Rubber Co., Ltd., this work contributes to our knowledge on the structural chemistry for the partial financial support and Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…All dimensions within the dibutphos ligand are normal, and they and other dimensions in the cation correspond well with those in related complexes (17,27,28). The geometry of the norbornadiene ligand is unexceptional (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Weighted leastsquares planes and selected torsion angles have been deposited as Tables SVI and S V I I .~…”
Section: Resultssupporting
confidence: 60%
“…All dimensions within the dibutphos ligand are normal, and they and other dimensions in the cation correspond well with those in related complexes (17,27,28). The geometry of the norbornadiene ligand is unexceptional (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Weighted leastsquares planes and selected torsion angles have been deposited as Tables SVI and S V I I .~…”
Section: Resultssupporting
confidence: 60%
“…Only recently has a practical protocol for its synthesis based on Ru‐catalysis been reported [17] . Although still not studied in detail, cumulative evidence suggests that the cage closure starts with the formation of an endo‐endo NBD dimer A , which evolves through a sequence of consecutive olefin insertion steps into B [16b, 18] . Final C−H oxidative addition followed by C−C reductive coupling are probably the last steps of the cycle, delivering 7 and regenerating the Ru active species (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…W ith fascinating highly symmetrical structures, carbocyclic cage compounds hold great promise for use as pharmaceuticals (e.g., amino-adamantanes), 1 energetic (e.g., nitrocubanes and CL-20), 2 and photonic/electronic materials (e.g., fullerenes). 3 In particular, HCTD (heptacyclo-[6.6.0.0 2,6 .0 3,13 .0 4,11 .0 5,9 .0 10,14 ]tetradecane) represents a unique class of cage molecules (Figure 1). 4 Analogous to cubanes and adamantanes, HCTD can be considered a distinct repository of cyclopentanes with D 2d symmetry.…”
mentioning
confidence: 99%
“…The prior mechanistic study 8 suggested that forming the undesired PCTD was initiated by a Ru−H-mediated 1,2addition of NBD. 10 Thus, it is logical to hypothesize that one key to promote the desired cage formation would be to avoid forming a ruthenium−hydride species, which indicates that choosing an appropriate ruthenium precatalyst would be critical. From a practical viewpoint, the study was initiated by examining a range of commercially available Ru(II) salts in combination with appropriate reductants, e.g., Mn or Zn.…”
mentioning
confidence: 99%
See 1 more Smart Citation